Generator of nanosecond pulses of pumping for an active pulse vision system in smoke and calculation of the its action range - Surikov, Андрей Валерьевич; Leshenyuk, Николай Степанович; Kuleshov, Владимир Константинович (Journal of Civil Protection, 2021)
Purpose. To develop a generator of nanosecond pulses for its use as part of an active pulse vision system under fire conditions and to analyze the effect of a decrease in the laser illumination pulse energy and the spectral sensitivity of the image converter system on the range of its action. Methods. The amplitude of the pulse generated by the developed generator was determined experimentally. The dependences of the change in the range of the active pulse vision system on the pulse energy of the laser emitter and the spectral sensitivity of the image-converter were determined by the calculation method. Findings. A generator of nanosecond pulses has been developed, which makes it possible to generate current pulses with an amplitude of up to 60 A, a duration at a level of 0.5 τ ≥ 2 ns, with edges of 3–1,4 ns. An analytical method for calculating the range of an active pulse vision system is presented, which makes it possible to determine this parameter taking into account the wavelength of the probing radiation and the dynamics of the fire. The results of a theoretical analysis of the range of an active pulse vision system when changing the energy of the laser illumination pulse and the spectral sensitivity of the image converter system are presented. Application field of research. The results of the study can be applied in the development of technical means designed to form an image of an object in smoke conditions.